KINERJA PADA BADAN LINGKUNGAN HIDUP KOTA PALU - Arlia, Arlia (Katalogis, 2015)
This research aims at analyzing and describing the performance of Agency for the Environment, Palu City as an organization. The analysis technique of this research is qualitative in which the obtained data was collected and classified, then it becomes a proof in this scientific research. This research uses primary data and secondary data. The result of this research shows that the performance of Agency for the Environment, has been categorized as good from productivity, service quality, responsivity, responsibility, and accountability. It is because the agency has run the principles of public administration and the employees have worked with good coordination. Its targets are always realized, and people always supervise the employees’ works so that it can be stable. Even though there are several works which are unsatisfying yet. The performance indicators used which showed non optimal result are productivity, service quality, and accountability. In productivity, the lack of leader’s presence in running programs which are usually done by secretary and position promotion is not based on educational background, while service quality is not optimal, facilities and infrastructures, and accountability; the lack of fund in running the programs, so that in the process of programs organization has not been reached.